Analytical Investigation of TAR for Enhancing Performance Using Varied Stack configuration and Varied Working Fluid - Shelke, Kamlesh S.; Wankhede, Uday S.; Yadav, Anand Kumar; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Thermoacoustic cooling, which uses sound waves to transfer heat, is an environmentally friendly and simple alternative to conventional refrigeration. Gas mixture adjustment to improve cooling performance is understudied compared to pure gas use. Previous studies focused on pure gas systems, but helium-argon combinations can boost thermoacoustic efficiency. Studying these gas mixtures` synergy could improve cooling efficiency.
Keywords: blend of gas; pure gas; nylon 6; thermoacoustic refrigeration